Nepalese Tourism Promotion Practices and its Effects - Awale, Sushil (Pragya Darshan प्रज्ञा दर्शन, 2025)
The spectacular landscape and diverse, exotic ethnic groups and cultures in Nepal represent considerable potential for tourism, but growth in the tourism industry has been not satisfactory relative to similar tourist destination. Nepal has spent massively on tourism promotion; however, there is no proper measurement of its effectiveness. The objectives of this study are to examine tourism promotion activities by Nepal in today’s digital age, to assess the effectiveness of the tourism promotion activities used to promote tourism in Nepal. This study is descriptive and analytical research design. This research based on survey of 401 tourism business operators. The study collected the perspectives of tourism business operators of Nepal on tourism promotion activities and their effectiveness. A survey of tourism operators revealed that website is the most effective way to increase awareness and create visits. WOM was most effective in creating revisits. This study also revealed, social media, tiktok, YouTube, Instagram, Facebook has replacing traditional promotional activities. Consumer survey on tourism promotion effectiveness could be done in future.